Intaglio Surface Dimension and Guide Tube Deviations of Implant Surgical Guides Influenced by Printing Layer Thickness and Angulation Setting. Issue 2 (15th January 2020) - Dalal, Nishchal; Ammoun, Rami; Abdulmajeed, Aous A.; Deeb, George R.; Bencharit, Sompop
Abstract: Purpose: To measure overall intaglio dimensional and tube deviations of implant guides printed at 50 and 100 µm layer thickness at 0°, 45°, and 90° angulation using a stereolithographic (SLA) printer. Materials and Methods: A surgical implant guide design from a subject missing a maxillary right central incisor, used as the original standard tessellation language (STL) were stereolithographically fabricated at each thickness and angulation, 50 and 100 µm layer thickness at 0°, 45°, and 90° angulation (n = 10 each group). The guide was then scanned using cone beam computed tomography. The digital imaging and communications in medicine (DICOM) scanned files were then converted to an STL format. The overall dimensional deviations of the intaglio surface and the positioning of the implant guide tube were then superimposed onto the original designed STL file using best‐fitting alignment. A t‐test and an F‐test as well as ANOVA followed by a post hoc t‐test were used to determine statistical significant differences (α = 0.05) for the intaglio surface and guide tube deviation, respectively. Results: The overall intaglio surface discrepancies (µm) printed at 0°, 45°, and 90° were 55.07 ± 1.36, 52.39 ± 2.09, and 61.02 ± 15.96 for 50 µm layer; and 98.38 ± 10.55, 84.47 ± 10.61, and 90.26 ± 5 for 100 µm layer with statistically significant differences for both t‐test and F‐test, p < 0.001. The maximal guide tube linear deviations (µm) printed at 0°, 45°, and 90° were 10.78 ± 3.84, 8.16 ± 3.68, and 12.57 ± 5.39 for 50 µm layer (ANOVA, p = 0.096); and 10.95 ± 5.23, 16.79 ± 4.97, and 22.63 ± 2.81 for 100 µm layer (ANOVA, p < 0.001). The maximal guide tube angular deviations (°) printed at 0°, 45°, and 90° were 1.29 ± 0.30, 0.64 ± 0.13, and 0.56 ± 0.21 for 50 µm layer (ANOVA, p < 0.001); and 1.57 ± 0.29, 0.86 ± 0.14, and 1.02 ± 0.31 for 100 µm layer (ANOVA, p = 0.034). There was a statistical difference in the deviations between 50 and 100 µm layer printing in all printed angulations except at 0° (t‐test, p = 0.05, p = 0.03, and p = 0.001 for 0°, 45°, and 90°) and linear deviations (t‐test, p < 0.001, p = 0.009, and p = 0.001 for 0°, 45°, and 90°). Conclusion: Printing at 50 µm layer reduces dimensional intaglio deviations in general and reduces tube angular deviations with different angulations of printing. However, the deviations were only ∼60 to 100 µm for the intaglio dimension deviations; and ∼0.04 to 0.26 mm and ∼0.25° to ∼2° for tube deviations.